Long term radial artery occlusion following distal or proximal transradial artery access in invasive cardiovascular procedures - Saboe, Aninka; Ibrahim, Maulana; Pranata, Raymond; Dewi, Triwedya Indra; Yahya, Achmad Fauzi (Universitas Brawijaya, 2025)
Background: Radial artery occlusion (RAO) is one of the most common consequences of transradial artery access (TRA) in invasive cardiovascular procedures; therefore, alternative approaches, such as distal radial artery access (DRA), emerged. This study compares proximal and distal radial access for long-term RAO. Objectives: This study compares long-term RAO incidence with proximal and distal radial access following invasive cardiovascular procedures. Material and Methods: This is a retrospective cohort study. The subjects comprised patients with heart disease who underwent invasive cardiovascular procedures using radial access at Dr. Hasan Sadikin General Hospital Bandung between July 2017 and December 2020. The patients were categorized into two groups based on their access type: proximal and distal. The incidence of long-term RAO was evaluated through Doppler ultrasound at least one-year post-TRA. Results: The study included 107 patients (proximal = 72 patients; distal = 35 patients). The mean age was 58.2 ± 8.26 years, with a predominance of male patients (79.4%) and smokers (65.4%). The majority of procedures were interventional (58.2%). Baseline characteristics were comparable between the two groups, except for selecting the access side, which was more prevalent on the left side in the distal group. Long-term RAO occurred in 8 patients (7.48%), with 7 cases (9.72%) in the proximal group and 1 case (2.86%) in the distal group (p=0.269). Conclusion: The study findings reveal no significant difference in the incidence of long-term RAO between proximal and distal radial access in invasive cardiovascular procedures.